TINGKAT LITERASI SAINS SISWA SMP MELALUI PEMBELAJARAN INQUIRY LESSON BERBANTUAN PETA KONSEP - Anik Astari; Lia Yuliati; Hadi Suwono (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
Science Literacy   has an important role in the teaching and learning process of science to apply and link the concepts. The study was conducted to describe the level of students' science literacy as well as to describe the changes after the implementation of  Inquiry Lesson learning aided by concept map. This research used embedded mixed method of experimental design model. The research instrument used was the instrument of intervention and measurement. Intervention Instrument consisted of a set of  learning  Instruction on Inquiry  Lesson aided by concept map while the measurement instruments include items on science literacy and  quiz items. The result of the study showed that the level of science literacy after the implementation of inquiry lesson aided by concept map reached Multidimensional category but mostly it reached Functional category. There is a marked difference in the science literacy of the students before and after the implementation of Inquiry  Lesson aided by concept map.Literasi sains memiliki peranan penting dalam pembelajaran IPA untuk menerapkan dan mengaitkan konsep-konsep. Penelitian dilakukan untuk mendeskripsikan tingkat literasi sains siswa serta perubahannya setelah pembelajaran Inquiry Lesson berbantuan peta konsep. Penelitian ini menggunakan rancangan mixed methods dengan embedded experimental design. Instrumen penelitian yang digunakan adalah instrumen intervensi dan pengukuran. Instrumen intervensi terdiri dari perangkat pembelajaran Inquiry Lesson berbantuan peta konsep. Instrumen pengukuran mencakup butir soal literasi sains dan butir soal kuis. Hasil tingkat literasi sains setelah pembelajaran Inquiry Lesson berbantuan peta konsep mencapai kategori Multidimensional namun paling banyak mencapai kategori Functional. Ada perbedaan yang nyata literasi sains siswa sebelum dan sesudah pembelajaran Inquiry Lesson berbantuan peta konsep.